A low-carbon evaluation framework for regional power systems - Ye, Jichao; Zhang, Hanbing; Huang, Hui; Hu, Xinwei; Wu, Xinhua; Qiu, Yi; Liao, Huanxin; Zhu, Yifan (Frontiers in Energy Research, 2024)
In order to arrive at a credible estimate of the power system's low-carbon level, this study develops a low-carbon evaluation framework for regional power systems. First, this study identifies the fundamental requirements that the index system for the low-carbon power system should follow and specifies the general direction for the index system's creation. Second, an evaluation model for carbon reduction ability is proposed by taking into account the basic aspects of generation side, grid side and load side of the power system. Then, a comparative evaluation model for the carbon reduction capability of multi-regional power systems is proposed to spatiotemporally compare the carbon reduction capability of different power systems. Next, a quantification method for the weights of low-carbon evaluation indicators is established based on the power system simulation of multiscenario scheduling and index sensitivity analysis method. Finally, a low-carbon comprehensive score for regional power systems is created by combining the evaluation results of the system's carbon reduction capacity with index weights. The practical research results in a region of Zhejiang province in China demonstrate that the proposed low-carbon evaluation system can provide a reasonable and feasible evaluation plan for the low-carbon construction of regional power systems.